Implementation of the Submission of Summons Reports through the Village Head in the Verstek Decision - I Gusti Agung Wisnu Murti; Ni Ketut Wiratny; I Nyoman Suandika (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The objectives of this thesis are to analyze the implementation of the submission of summons reports through the village head in the verstek decision and to analyze the obstacles to the implementation of the submission of summons reports through the village head in the verstek decision. The type of research used in this study is empirical juridical legal research. In empirical juridical research, law, as law in action, is described as an empirical social phenomenon. Empirical legal research, also known as sociological legal research, is legal research that examines law by conceptualizing it as actual behavior, an unwritten social phenomenon experienced by everyone in social relationships. The results of this study found that the implementation of the submission of summons reports through the village head in the verstek decision is related to the implementation of summons in civil cases at the Bangli District Court. Since the issuance of PERMA Number 7 of 2022, there has been a change in the implementation of the submission of summons reports, from the conventional summons issued through a bailiff to now using registered mail. There are no sanctions or penalties for the sub-district or village if they do not directly convey the summons given, and the requirement for postal officers to convey the village head also faces time constraints and the busyness of the postal officers themselves, who must adjust the workload of postal delivery, which of course has a postal delivery target aligned with the opening or service hours of the post office or sub-district office.